Images of the Saturn Hexagon before Voyager 1 - Ferreri W.; Codebò M.; Bubbi B. (Archaeoastronomy and Ancient Technologies, 2021)
In 1981 the Voyager 1 probe photographed – and later the Cassini probe confirmed – a hexagonal vortex on Saturn's North pole. This cloud features extends for almost 30,000 km keeping its shape unchanged as it rotates with the planet. But, since we see it very foreshortened, it appears to us with the greater extension of 4" and the smaller one of 1.3": this makes it virtually visible from Earth with telescopes. And in fact, after the first images of Voyager 1, many amateur astronomers managed to photograph it even with modest instruments of a few tens of centimeters in diameter, but using digital photography techniques. We therefore wondered if the hexagon had been seen by astronomers of the past mainly using their professional telescopes. Our research gave positive results: E.E. Barnard (with the Yerkes' refractor) and E.M. Antoniadi (earlier with Juvisy's and later with Meudon's refractors) pictured it since the end of the 19th century, but they never mentioned it in their writings, probably because it was at the limit of visibility and it was impossible to explain the hexagon with the knowledge of that time. These pictures prove that the hexagon has been present and active for at least 124 years on the North pole of Saturn, similar to the (longer-lived) red spot of Jupiter.